Network pharmacology study of Citrus reticulata and Pinellia ternata in the treatment of non-small cell lung cancer - Li, Changyang; Lu, Hongxiu; Jiang, Xianghu; Guo, Xuefeng; Zhong, Hua; Li, Huijie (Cellular and Molecular Biology, 2022)
It has been recognized that Citrus reticulata and Pinellia ternata have a good therapeutic effect on NSCLC. However, the potential mechanism of C. reticulata and P. ternata in the treatment of NSCLC based on network pharmacology analysis is not clear. The “Drug-Component-Target-Disease” network was constructed by Cytoscape, and the protein interaction (PPI) network was constructed by STRING. Our study indicated that 18 active ingredients of C. reticulata and P. Ternata were screened from the TCMSP database, and 56 target genes of C. reticulata and P. Ternata for the treatment of NSCLC were identified, and we constructed the “Drug-Component-Target-Disease” network. In this study, we screened 56 PPI core genes to establish a PPI network. We concluded that the network pharmacology mechanism of the effect of C. reticulata and P. Ternata on NSCLC may be closely related to the protein expressed by TP53, ESR1, FOS, NCOA3 and MAPK8, and these may play the therapeutic roles by regulating the IL-17 signaling pathway, antigen processing and presentation, microRNAs in cancer and endocrine resistance.